Effectiveness of the program “Annotations, that speak for you” in the knowledge, attitudes and practices of nursing professionals in nursing annotations according to the SOAPIE model in the hospitalization services of Hospital II Vitarte, Lima - Aguilar Campos, Edith (2019)
Objective: To determine the effectiveness of the program “Annotations, which speak for you” in the knowledge,attitudes and practices of nursing professionals, in nursing notes according to the SOAPIE Model, of thehospitalization services of Hospital II Vitarte. Materials and methods: Quantitative study; Pre-experimentaldesign with a before and after, longitudinal cut. Twenty-four nursing professionals from the hospitalizationservices of Medicine, Pediatrics, Surgery and Intensive Surveillance Unit participated; To whom three types ofinstruments were applied: a questionnaire to measure knowledge, the scale of attitudes Likert type and the guideof observation to evaluate the practice. Results: The educational program improved the level of knowledge aboutnursing annotations in the SOAPIE model of nursing professionals, increasing the average before and after theintervention from 20.7 to 25.0 points (p-value = .000), (P-value = .000) and improved the nursing record practice,increasing the average score from 6.33 to 10.21 (p-value = .6). 000). Conclusions: The educational program“Anotaciones, que tallan por ti” was effective in the knowledge, attitudes and practices according to the SOAPIEmodel, in the Nursing professionals of Hospital II Vitarte-EsSalud.